VALIDATING A LISTENING COMPREHENSION QUESTIONNAIRE: EXPLORING THE CINDERELLA SKILL IN ESL THROUGH AN ISLAMIC PERSPECTIVES - Wan Afiqah Anis Wan Ahmad; Mohamad Azrien Mohamed Adnan; Wan Rohani Wan Mokhtar; Suryani Awang, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Listening comprehension has long been the Cinderella skill of language learning though it is fundamental yet often undervalued in second language acquisition (SLA). This is particularly evident among Islamic Studies students, who must navigate both Arabic and English language in their educational journey. Despite its pivotal role in academic success and cognitive engagement, research on listening strategies and metacognitive awareness within this learner population remains limited. Addressing this gap, this study developed and validated a comprehensive research instrument to assess listening self-efficacy, emotional engagement, metacognitive awareness and listening comprehension among ESL learners in Islamic Studies programs. A systematic expert validation process was conducted with the experts in SLA, Islamic education and assessment methodology, ensuring the instrument’s content validity and reliability. Then, the final version comprised 45 validated items across five constructs. The Content Validity Index (CVI) exceeded the 0.7 threshold, confirming its robustness, while Cronbach’s Alpha analysis (α > 0.7) demonstrated strong internal consistency. The refined instrument effectively captures both cognitive and affective dimensions of listening comprehension, making it a valuable tool for assessing listening challenges in ESL especially among the Islamic study students. This study makes significant theoretical and pedagogical contributions. It highlights the overlooked importance of listening among Islamic Studies students, reinforcing the need for explicit listening strategy instruction to enhance their linguistic proficiency. The findings align with contemporary SLA theories and Islamic traditions that emphasize active and mindful listening as a means of intellectual and spiritual growth. Future research should explore the instrument’s applicability across diverse educational contexts, particularly where multilingual learners engage with both religious and academic discourse. By bridging SLA research, listening skill and Islamic perspective, this study advances understanding of listening comprehension in ESL settings and from the Islamic lens, offering insights for curriculum design, pedagogical strategies and professional development.